PENGARUH ACADEMIC EMOTIONS DAN SCHOOL BELONGING TERHADAP STUDENTS’ LIFE SATISFACTION PADA SISWA MENENGAH PERTAMA - Raden Wachyu Zakia Fadilah; Sri Maslihah; Ifa Hanifah Misbach (JURNAL PSIKOLOGI INSIGHT, 2018)
The aim of this study was to determine the influence of academic emotions and school belonging toward students’ life satisfaction of students of state junior high school in Bandung. The approach used is a quantitative approach by using causality technique research. Cluster random sampling used as sampling technique. 471 students of state junior high school in Bandung completed the adaptation of Achievement Emotions Questionnaire (AEQ), adaptation of Psychological Sense of School Membership (PSSM), and adaptation of Multidimensional Students’ Life Satisfaction Scale (MSLSS). Analyses using linear and multiple regression revealed (1) there is a significant effect of positive academic emotions to students’ life satisfaction, (2) there is a significant effect of negative academic emotions to students’ life satisfaction,(3) there is a significant effect of school belonging to students’ life satisfaction, (4) there is a significant effect of positive academic emotions and school belonging to students’ life satisfaction, and (5) there is a significant effect of negative academic emotions and school belonging to students’ life satisfaction.